Social media data as a gateway to victims’ experiences - Aguerri, Jesús C. (The crime data handbook, 2024)
In recent decades, we have witnessed how a large part of our lives, our economy and our institutions has transitioned to cyberspace. The digitalization of our societies has led to the internet becoming a sort of new public space. Numerous authors have addressed how this has changed criminal realities and their inner structures and have pointed to the methodological and theoretical challenges that cybercrime poses to criminology. But this digital environment also offers victims a new way to share their experiences, both individually and collectively, specifically on social media. Such is the case of, for instance, the #MeToo movement, which has become an important source of data on victims and their experiences. This information is valuable for criminology both for its own sake and as a link to criminological phenomena, such as fear of crime or trust in justice systems. This chapter addresses the potential of social media as a way of accessing the phenomenon of victimization, with special emphasis on the techniques that have proven to be most useful for the collection and analysis of this type of data.